Bottom up Internationalization Strategy – Case Study on Internationalization at Universitas Muhammadiyah Yogyakarta (UMY) - Dr. Achmad Nurmandi, M.Sc. (University ofApplied Science, 2013)
This paper describes the process of internationalization at Universitas Muhammadiyah Yogyakarta (UMY) through organizational transformation as a part of a personal action project of the International Dean’s Course. In 2009, university management changed the organizational structure to support university internationalization by setting up an international office. This organizational transformation affects the decision making process, especially related to internationalization.